The Effect of Tax Incentives, Trust in Tax Authorities, And Fiscus Services Quality on Msme Taxpayer Compliance During Covid- 19 Pandemic - Ayu Khairunnisa; Lilis Maryasih; Nuraini A (Budapest International Research and Critics University, 2022)
This study aimed at testing the influence of tax incentive, trust on tax authority, and fiscus service quality on micro, small, and medium enteprises (MSME) tax payer compliance during the covid-19 pandemic. This study also examined the differences in the compliance of MSME taxpayers who take advantage of incentives with MSME taxpayers who do not take advantage of tax incentives. By using the probability sampling technique, 394 MSME were selected from 26,019 population of MSME registered in Aceh Regional Office of Directorate General of Taxation as the sample of this study. The results revealed that tax incentives, trust on tax authority, and fiscus service quality have positive and significant influence on SMSE tax payer compliance during the covid-19 pandemic. The result also imply that 71.2% MSME tax payer compliance covid-19 pandemic in Aceh Province was influenced by tax incentives, trust on tax authority, and fiscus service quality. While 28.8% SMSE tax payer compliance with the covid-19 pandemic in Aceh Province was determined by other factors out of this study.